Use of a Portable Particle Counter to Analyze Particle Stability Time in a Biological Safety Cabinet (BSC) - Putri, Herlina Candra; Cahya Nugraha, Priyambada; Yulianto, Endro; Bhatt, Ashish (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Biological Safety Cabinet (BSC) is a laboratory work area with air ventilation that has been engineered to protect workers working with material samples, the environment and material samples from the possible danger of contamination or causing the spread of pathogenic bacteria or viruses. The purpose of this study is to analyze the stability of the time required for the BSC to reach the condition of no particles in the BSC space. This is done by making a module using the PMS7003 sensor to detect the number of particles. This study uses the Arduino Mega system for data processing and then displays it in the form of graphs and numbers. In the condition of the number of particles of 162,965, the time required for the BSC is 29 seconds, while in the condition of the number of particles of 186,408, the time required is 38 seconds. So it is known that if the number of particles in the BSC space is more and more particles in the BSC space, the longer it takes for the BSC to reach the no-particle condition. BSC that uses a single fan blower cannot achieve a stable number of particles simultaneously.